Reactivation of paremia with the name of KYIV in modern communication - Syzonov , Dmytro (Current issues of Ukrainian linguistics: theory and practice, 2024)
The article describes the process of reactivation of paremies with the oikonym "Kyiv" in Ukrainian-language communication. The status of paremias in modern linguistics is considered, various approaches to the understanding and scientific interpretation of paremia units are presented, in particular, their study in a broad perspective is necessary – as sayings and proverbs, precedent sayings, aphorisms, etc.The author emphasizes the most commonly used paremic constructions in Ukrainian, such as язик до Києва доведе, Київ – мати міст руських, як до Києва рачки, etc. On the material of lexicographic works, artistic texts of Ukrainian literature, spoken and media communications, parallels are drawn with the usage and functional possibilities of paremys with the oikonym "Kyiv". It was followed how paremic units with the element "Kyiv" in their structure changed and transformed in mass communication.The status of media paremia and its discursive parameters are also determined. A separate locus of the article is devoted to new phraseological units that appear in mass communication. Thus, paremias are actualized in various types of media, in the structure of which the lexeme "Kyiv" is a key manipulator: Kyiv holds the blow; Maidan starts from Kyiv; take Kyiv in three days; This is Kyiv, baby; KyivNotKiev, etc. The "discussion" of such paremias is also an indication of the dynamism of such constructions in mass communication, which is motivated by the needs of the media to influence the recipients.It was found that the occurrenceq of paremies with the oikonym "Kyiv" is a frequent phenomenon associated with the status of the city in the geopolitics, economy, and culture of Ukraine. Such a complex of extra-lingual factors indicates the dynamism of the structure and stylistic possibilities of paremias, capable of being actualized in new communicative conditions.
Keywords: paremias; phraseology; oikonym; Ukrainian communication; onim; mass communication; modern linguistics.